Reducing potentially fatal errors associated with high doses of insulin: a successful multifaceted multidisciplinary prevention strategy. Issue 7 (12th April 2011) - Dooley, Michael J; Wiseman, Meredith; McRae, Amy; Murray, Danielle; Van De Vreede, Melita; Topliss, Duncan; Poole, Susan G; Wyatt, Sue; Newnham, Harvey
Abstract : Background: Insulin is a high-risk medicine which may cause significant patient harm or death when given incorrectly. A 10-fold error in administered insulin dose commonly occurs when the abbreviation 'u' is used for 'units' and subsequently misinterpreted as a 'zero.' Method: A multidisciplinary working party was convened and mapped insulin prescribing, dispensing and administration. All inpatient orders above 25 units for short-acting insulin and 50 units for other insulin require validation by an additional source. Educational strategies to support adherence to the guideline and product-labelling alerts were developed. Results: Implementation occurred in August 2008 across the three hospital sites. In 90 weeks after implementation, there were 150 patients identified in which 200 high doses of insulin were prescribed (>25 units for short-acting insulin and 50 units for other insulin). There were eight instances where high doses of insulin were prescribed in error but were detected and rectified through the new validation process. There were 12 dosing errors that occurred, including two 10-fold dosing errors. In contrast, seven major errors resulting in excessive insulin administration were identified over a 2-year period prior to the introduction of the insulin high-dose validation system. Conclusion: A structured validation process was successful in reducing incorrect prescription and administration of high-dose insulin and has reduced the risk of associated fatalities or significant patient harm. Consideration should be given to adopting this process in any setting where insulin is prescribed and administered.